Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1093/nar/gkx477
|View full text |Cite
|
Sign up to set email alerts
|

Major hnRNP proteins act as general TDP-43 functional modifiers both in Drosophila and human neuronal cells

Abstract: Nuclear factor TDP-43 is known to play an important role in several neurodegenerative pathologies. In general, TDP-43 is an abundant protein within the eukaryotic nucleus that binds to many coding and non-coding RNAs and influence their processing. Using Drosophila, we have performed a functional screening to establish the ability of major hnRNP proteins to affect TDP-43 overexpression/depletion phenotypes. Interestingly, we observed that lowering hnRNP and TDP-43 expression has a generally harmful effect on f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
58
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 80 publications
(91 reference statements)
7
58
0
Order By: Relevance
“…In particular, the inflammatory proteins TNF, TNFRSF9, and ICAM1 were upregulated by the silencing of hnRNP Q, likewise to what observed with silencing of TDP-43 and DAZAP1 (Appocher et al, 2017). TNF is a pro-inflammatory cytokine that is expressed in the central nervous system and its soluble form can promote neuronal inflammation, occurring in neurodegenerative conditions such as ALS, multiple sclerosis, Alzheimer's and Parkinson's diseases (McCoy and Tansey, 2008).…”
Section: Discussionsupporting
confidence: 58%
“…In particular, the inflammatory proteins TNF, TNFRSF9, and ICAM1 were upregulated by the silencing of hnRNP Q, likewise to what observed with silencing of TDP-43 and DAZAP1 (Appocher et al, 2017). TNF is a pro-inflammatory cytokine that is expressed in the central nervous system and its soluble form can promote neuronal inflammation, occurring in neurodegenerative conditions such as ALS, multiple sclerosis, Alzheimer's and Parkinson's diseases (McCoy and Tansey, 2008).…”
Section: Discussionsupporting
confidence: 58%
“…A bioinformatic search (data not presented) for potential binding of Caz/dFus protein with transcripts of the positive and negative modulators of Ras signaling, whose transcript levels were found to be enhanced or reduced (Fig.6) when hsrω nuclear transcript levels were altered in activated Ras background, revealed that many of these transcripts indeed carry binding sites for Caz/dFus. Significantly, another hnRNP family member which interacts with omega speckles and with Caz/dFus protein is the TDP-43 (dTBPH) (Appocher et al, 2017;Coyne et al, 2015;Piccolo et al, 2018;Romano et al, 2014). The Caz/dFus and TDP-43 also interact with Fmr1 RBP, and the three of them are involved in complex interactions with variable consequences for processing, translatability and stability of diverse mRNAs (Appocher et al, 2017;Coyne et al, 2015;Piccolo et al, 2018;Piccolo and Yamaguchi, 2017;Romano et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, another hnRNP family member which interacts with omega speckles and with Caz/dFus protein is the TDP-43 (dTBPH) (Appocher et al, 2017;Coyne et al, 2015;Piccolo et al, 2018;Romano et al, 2014). The Caz/dFus and TDP-43 also interact with Fmr1 RBP, and the three of them are involved in complex interactions with variable consequences for processing, translatability and stability of diverse mRNAs (Appocher et al, 2017;Coyne et al, 2015;Piccolo et al, 2018;Piccolo and Yamaguchi, 2017;Romano et al, 2014). It is significant that like the many other RBPs, each of these three genes produce multiple transcripts and multiple protein products (http://Flybase.org).…”
Section: Discussionmentioning
confidence: 99%
“…The strong genetic and pathological links between TDP-43 and neurodegenerative disease have stimulated intense interest in elucidating the relationships between its normal and pathological functions (Taylor et al, 2016). Although TDP-43 was originally identified and named for its ability to bind to HIV-1 long terminal repeat DNA, it is now understood that TDP-43 is ubiquitously expressed in all cell types and plays an important physiological role in regulating the splicing of multiple endogenous human mRNAs (Appocher et al, 2017;Conlon and Manley, 2017;Ling et al, 2015;Tollervey et al, 2011).…”
Section: Introductionmentioning
confidence: 99%